Mechanisms of prezygotic post-pollination reproductive barriers in plants - Wang, Ludi; Filatov, Dmitry A. (Frontiers in Plant Science, 2023)
Hybridisation between individuals of different species can lead to maladapted or inviable progeny due to genetic incompatibilities between diverging species. On the other hand, mating with close relatives, or self-fertilisation may lead to inbreeding depression. Thus, both too much or too little divergence may lead to problems and the organisms have to carefully choose mating partners to avoid both of these pitfalls. In plants this choice occurs at many stages during reproduction, but pollen-pistil interactions play a particularly important role in avoiding inbreeding and hybridisation with other species. Interestingly, the mechanisms involved in avoidance of selfing and interspecific hybridisation may work via shared molecular pathways, as self-incompatible species tend to be more 'choosy' with heterospecific pollen compared to self-compatible ones. This review discusses various prezygotic postpollination barriers to interspecific hybridisation, with a focus on the mechanisms of pollen-pistil interactions and their role in the maintenance of species integrity.